Petroleum Revenue Management In Ghana: The Epoch Of High Expectation In Perspective - Abraham, Kow Kwegya Amissah (Journal of Sustainable Development Law and Policy, 2025)
The avoidance of resource curse is, in part, dependent on the management and administration of realized revenue from the exploration of its natural resource. This article evaluates the existing fiscal regime and the regulatory frameworks that Ghana established to manage its petroleum revenue from 2010 to 2013. The restrictive period accounts for the era where Ghanaians showed high expectations of increased benefits from oil. In this vein, the article analyses the preparedness reflected in the policy framework to manage accrued revenue and, by extension, the expectation of citizens on improved living conditions. This article established that existing mechanisms, legislation, and checks and balance procedures to manage petroleum revenues are not the final steps at ensuring sustainable development. Two crucial factors play a decisive role in this regard. First is the extent to which accrued revenue is expended in critical areas of the economy for accelerated growth. Second is the commitment to, and establishment of, strong public institutions to enforce the relevant regulations.